Ex Ante Inequality of Opportunity in Health among the Elderly in China: A Distributional Decomposition Analysis of Biomarkers - Lanlin Ding; Andrew M. Jones; Peng Nie (Institute of Labor Economics (IZA), 2020)
We present a comprehensive analysis of ex ante inequality of opportunity (IOp) in health among Chinese adults aged 60+ and decompose the contributions of different sets of circumstances. Data are drawn from the 2011 and 2015 waves of the China Health and Retirement Longitudinal Study (CHARLS) linked with the 2014 CHARLS Life History Survey. We use a range of blood-based biomarkers, and apply a re-centered influence function (RIF) approach and a Shapley-Shorrocks decomposition to partition the contribution of circumstances across different quantiles of the biomarker distributions. We find that IOp accounts for between 3.75% and 29.57% of total health inequality in old age across the range of biomarkers. Shapley-Shorrocks decompositions show that spatial circumstances such as urban/rural residence and province of residence are the dominant determinants of IOp for most of the biomarkers. Distributional decompositions further reveal that the relative contributions to IOp in health of household socioeconomic status and health and nutrition conditions in childhood increase towards the right tails of the distribution for most of the biomarkers, where the clinical risk is focused.
Keywords: D63; I12; I14; 330; biomarkers; CHARLS; China; inequality of opportunity; Shapley-Shorrocks decomposition; unconditional quantile regressions